Criação de gado na Reserva Extrativista Tapajós-Arapiuns, ameaça ou necessidade? Caracterização ambiental, social e financeira para subsidiar ações de gestão - Spínola, Jackeline Nóbrega (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
The development of livestock activities within Extractive Reserves in the Amazon has been a source of controversy and debate in the environmental area since the establishment of the SNUC law. The history of the extractive movement had as its main fight flag, the "ties", as a strategy to combat deforestation and maintenance and right to use the territory. Regardless of the advances of the movement, it is a fact that livestock activity has developed over the last 20 years, as the predominant use in deforested areas in the Amazon, including within Conservation Units-CU. The objective of this work was to evaluate the cattle raising activity in the Tapajós Arapiuns Extractive Reserve, looking at to social and financial point of view, through the elaboration of a census diagnosis with the livestock farmers of the Conservation Unit, as well as of the environmental impacts caused by the formation of pastures based on the analysis of the data provided by INPE / Projeto TerraClass, with a view to subsidizing management actions. As main results on the environmental impacts of the activity in the CU, it is highlighted that more than 90% of the area is preserved, even in the face of intense population occupation. At present, only 0.35% of the area of the Extractive Reserve is destined to pasture, and this formation occurred mainly under already consolidated areas. The verified stocking rate, in the order of 1.15 head / ha, indicates that there is no overgrazing phenomenon. The sanitary issue has been highlighted as one of the main problems due to the modality of creation of the loose cattle, with free access to the water courses and to the urban areas of the communities. The diagnosis showed that 193 beneficiaries are responsible for the creation of 2,718 animals in the Resex, with 1/3 of them having only one animal used for transportation, and the rest of the breeders between 2 and 150 heads. The average size of the herd per breeder, rotates around 14 heads. It is worth noting the strong interest of 62% of breeders in developing other crops or farming practices, demonstrating the complementarity characteristic of the activity. Another relevant aspect is related to their economic and social economic importance, since 60% of breeders reported that their herds supply Resex communities, that is, they are marketed within the CU itself. In view of the above, it is concluded that the cattle raising activity in the Tapajós-Arapiuns Extractive Reserve can be considered subsistence due to the size and modes of production identified. It has financial, social and cultural relevance for the creative beneficiaries or not. And finally, it is not the main vector of deforestation in UC, and its contribution is practically irrelevant. The future of the Resex Tapajós Arapiuns and other Extractive Reserves in the Amazon, should not be based on the dichotomy: livestock! Yes or no? Rather, it should be based on the sustainability of practices of use of existing environmental resources
Keywords: Reserva extrativista; Tapajós-Arapiuns; Criação de gado; Gestão de unidades de conservação